Revolusi Pendidikan: Kurikulum Merdeka Solusi Problematika Belajar? - Vahira Febri Herina Putri; Masduki Asbari; Salma Adzka Khuzaima Khanza (AGUSPATI RESEARCH INSTITUTA, 2023)
The purpose of this study is to deepen understanding, and introduce innovations in learning methods that give students the freedom to explore, collaborate and create solutions. This study report uses a descriptive qualitative method by doing simak catat because the data source is obtained by listening to the oral narration from the Youtube channel Sobat Baru entitled